Left-right Model for Dark Matter - Phung, Dong Van; Do, Huong Thi (Communications in Physics, 2018)
We argue that dark matter can automatically arise from a gauge theory that possesses a non-minimal left-right gauge symmetry, SU(3)_C \otimes SU(M)_L \otimes SU(N)_R \otimes U(1)_X, for (M,N)=(2,3), (3,2), (3,3), …, and (5,5)